MAKNA YANG TERKANDUNG DALAM GERAKAN TARI GANDHONG SEBAGAI BUDAYA KHAS KABUPATEN TRENGGALEK - mawadah, ilma maretiana; Setyawan, Bagus Wahyu (Institut Seni Indoensia Surakarta, 2022)
Culture can give a sense of identity to group members. One of the things that is born from culture is art. Art can be used as an icon or identity of a region. Like in Trenggalek which has the art of Gandhong Dance which is a typical culture of the area. Culture, especially art, usually arises because of the background events. From this statement, researchers are interested in examining more deeply the origins and meanings contained in the series of movements in each stage of the Gandhong Dance. The method used is descriptive qualitative with data collection techniques through interviews and documentation studies. From the research that has been done, Gandhong Dance is an art that was born in Bangun Village, Munjungan District, Trenggalek Regency which tells about the activities carried out by farmers. This dance has four acts in the show, each act has its own meaning and is sequential from one act to another so that it resembles a storyline. The series of motions in act one tell the events of clearing land, the series of motions in act two tell the events of cultivating land, planting, weeding, and harvesting. The series of motions in the third act tells the events of the arrival of pests that attack the plants, and the series of motions in the last act tells of the farmers who kill and repel pest. Keyword: Meaning, Movement, Gandhong Dance, Culture, Trenggalek.